The management of dog bite injuries of genitalia in paediatric age - Mirko Bertozzi; Antonino Appignani (Wolters Kluwer Medknow Publications, 2013)
Dog bite injuries are common in children and represent an important health-care problem. Most dog bite injuries involve the face or an extremity. Victims tend to seek medical care quickly. Dog bites to the external genitalia are rarely reported, but they potentially result in morbidity if improperly managed. Morbidity is also directly related to the severity of initial wound. Guidelines for the management of dog bites include irrigation, dιbridment, antibiotic therapy, consideration of tetanus and rabies immunisation and suture of wounds or surgical reconstruction. Literature review was conducted and focused to analyze the management of dog bite lesions involving external genitalia.